Impact of using cover crop on predation slug on corn in Pennsylvania - Beloghi, Cristhoper; Bullock, James M (Institute for Research and Community Service (LPPM), Universitas Islam Madura, Indonesia, 2024)
Farmers in Pennsylvania face a significant obstacle in the form of slug insect management. Aims of this study to determine impact of using cover crop against slug attacks in Pennsylvania. This study collaborated with a Pennsylvania regional no-till farming unit to assign three treatments to each farmer: no crop cover (CA), plastic mulch cover (CP), green rye cereal cover (CRH), and dry rye cereal cover (CRK). The experiment was carried out in May – August in 2023. The use of rye cereal cover crops, both in green and dry form, can also have the potential to reduce slug pests. These plants provide shelter and breeding ground for natural enemies of slugs. Plant residue mulching in conservation farming practices provide an effective and sustainable slug pest management strategy. The use of rye cereal can be a reference for farmers in anticipating slug pests in an environmentally friendly manner.